An Active Role for Steroid-binding Globulins: An Update - Caldwell, J. D.; Jirikowski, G. F. (Hormone and Metabolic Research, 2013)
It has been 7 years (can it really be that long?) since we co-edited a volume (#38) of Hormone and Metabolic Research that focused on evidence that steroid-binding globulins play an active role in the actions of steroids. There has been considerable progress in identifying the location, the physiological actions, and of determining the role of binding globulins in the actions of steroids and identifying a membrane-associated receptor for a binding protein since then and this review will discuss this progress.
Keywords: sex hormone-binding globulin; corticosteroid-binding globulin; vitamin D-binding globulin; RBP receptors; elastase nongenomic steroid effects